Bipolar Disorder Of The Main Character As Seen In The Touch With Fire Movie By Paul Dalio - Andi Setiawan; Alfian Alfian; Firdiansyah Firdiansyah (English Literature Department, Adab and Humanities Faculty, 2021)
The aim of this research is to analyze Bipolar Disorder of Marco and Carla in Touched with Fire Movie by Paul Dalio. The purpose of this research are (1) To find out the types of Bipolar Disorder experienced by Marco and Carla in the Touched with Fire film (2) To find out the causes of Bipolar Disorder that happened in the Touched with fire film. This research uses psychological approach by Endraswara about Bipolar Disorder, theory of types of Bipolar Disorder by Boulvard Wilson and the cause of Bipolar Disorder by Michael Wilson Passer and Smith Ronald. The method used in analyzing the problem in this research is a qualitative descriptive method. The results of this study are that Marco and Carla experienced some degree of mania and also some symptoms of depression, and also mixed episode. The causes of Bipolar Disorder in the film are psychological factors and environmental factors. Marco and Carla experience periods of unusually intense emotion, changes in sleep patterns and activity levels and characteristic behavior without recognizing their likely harmful or undesirable effects.